NEW NORMAL CAMPAIGN OF COVID-19 ADVERTISEMENTS BY WHO: A MULTIMODAL STUDY - Asmah Boru Munthe; T Thyrhaya Zein; T Silvana Sinar (English Review: Journal of English Education, 2023)
After Covid-19 outbreak spread around the world, many advertisements campaign the new normal life. WHO made some rules how the way to life in new normal. This research aims to describe verbal and visual elements in the new normal campaign of Covid-19 advertisements by WHO. The research used qualitative descriptive research with an interactive model. The technique of collecting data was documentation. The researcher used Ideational Function to analyze verbal elements and Grammar Visual Design Theory to analyze visual elements. Based on the finding, there were three dominant elements in verbal elements. First, the dominant participant was the goal (19). Second, the dominant process was material (20). Third, the dominant circumstance was manner (4). Meanwhile, there were also three dominant elements in visual elements. First, the dominant representational was narrative (17). Second, the dominant elements in interactive were offer (19), medium long shot (6), oblique (16), and eye level (17). Third, the dominant element in compositional was salience (54). The conclusion was the visual elements were more dominant than the verbal elements. The visual element showed many images that made the readers understand by looking at them and the verbal elements were just additional information to the readers to not get misunderstood the images. Thus, the verbal elements correlated with the visual elements to convey the meaning from advertisements to the viewers